The Agrobiodiversity Index: Methodology Report v.1.0. - Bioversity International (Bioversity International, 2018)
The Agrobiodiversity Index is an innovative tool that measures the current state of agrobiodiversity in markets and consumption, in agricultural production, and in genetic resource management, and the extent to which commitments and actions at country, company and project level support sustainable use and conservation of agrobiodiversity. Status indicators are scored based on spatial global data sets and national data sets accessed through global databases at United Nations agencies. Action indicators are scored based on country reports, such as those from the World Information and Early Warning System on Plant Genetic Resources for Food and Agriculture (WIEWS) and in the State of the World Biodiversity for Food and Agriculture, both compiled by the Food and Agriculture Organization of the UN (FAO), as well as other spatial datasets. Commitment indicators are scored based a text-mining tool that analyzes policies, strategies and other national legislation, retrieved from the FAO’s legislation and policies database, FAOLEX. The Agrobiodiversity Index has 22 indicators, comprising 3 commitment indicators, 4 action indicators and 15 status indicators.